2022
DOI: 10.3389/fsufs.2022.1059235
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative risk assessment of salmonellosis in Cambodian consumers through chicken and pork salad consumption

Abstract: Salmonella is a globally important foodborne bacterial pathogen that poses a high risk to human health. This study aimed to estimate the risk to Cambodian consumers from acquiring salmonellosis after consuming chicken and pork salad, using a quantitative microbial risk assessment (QMRA). Chicken and pork salads are typical Cambodian dishes containing raw vegetables and boiled chicken meat or pork. As previously described, chicken meat and pork samples (n = 204 of each) were collected from traditional markets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(70 reference statements)
0
3
0
1
Order By: Relevance
“…[ 36 , 37 ], E. coli O157:H7 [ 38 ], and Salmonella sp. [ 39 ]; for the first two pathogens, the severity was set to moderate, while for Salmonella sp., the choice was set to “mild”. The risk ranking was 52 for Campylobacter spp.…”
Section: Risk Ranger In the Food Company Contextmentioning
confidence: 99%
“…[ 36 , 37 ], E. coli O157:H7 [ 38 ], and Salmonella sp. [ 39 ]; for the first two pathogens, the severity was set to moderate, while for Salmonella sp., the choice was set to “mild”. The risk ranking was 52 for Campylobacter spp.…”
Section: Risk Ranger In the Food Company Contextmentioning
confidence: 99%
“…Prevalensi kontaminasi Salmonella pada daging ayam telah dilaporkan di berbagai negara, antara lain China, Kolombia, Korea Selatan, Ethiopia, dan Kamboja (Yang et al, 2011;Donado-Godoy et al, 2014;Rortana et al, 2022 ;Chen dkk., 2010;Yoon dkk., 2014). Penelitian juga menyoroti pentingnya prosedur pembersihan dan disinfeksi menyeluruh dalam mengurangi risiko kontaminasi Salmonella pada karkas ayam (Cardinale et al, 2005).…”
Section: Pendahuluanunclassified
“…The expected number of cases of infection per year for the whole UAE population Cases RiskOutput (Calculation = P inf,year × number of UAE inhabitants (10.2 × 10 6 , based on Worldometer data [25] The calculated exposure (D) was used to estimate the probability of infection with Salmonella per day (P inf,day ), using a beta-Poisson dose-response formula. The model's parameters and values were drawn based on the risk assessment of Salmonella in poultry products, representing a commonly accepted dose-response formula used previously in the risk assessments of Salmonella in leafy greens [7,24]. Then, the probability of infection per individual per year (P inf,year ) was calculated as P inf,day × 365.…”
Section: Risk Assessment Model Developmentmentioning
confidence: 99%
“…Based on epidemiological investigations, it has been revealed that non-typhoidal Salmonella is among the frequent bacterial pathogens responsible for foodborne outbreaks associated with fresh salad vegetables [ 5 , 6 ]. The prevalent hypothesis is that consuming raw salad vegetables poses a risk of salmonellosis due to cross-contamination arising from the preparation of food with other contaminated items, such as raw chicken [ 7 ]. However, numerous studies have reported the detection of Salmonella on raw fresh produce at the retail level before food preparation [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%